A method for preparing aluminum nitride ceramics by adhesive injection molding technology

The aluminum nitride powder is modified and printed through adhesive jet molding technology, combined with vacuum glue discharge, impregnation and sintering treatment, which solves the problem of difficulty in preparing high-performance aluminum nitride ceramics in the prior art, and achieves efficient and economical preparation of aluminum nitride ceramics.

CN116986910BActive Publication Date: 2025-04-15GUANGDONG UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311012509.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-11
Publication Date
2025-04-15
Estimated Expiration
2043-08-11

AI Technical Summary

Technical Problem

There is no relevant information on the preparation of aluminum nitride ceramics by adhesive spray forming technology in the prior art, which makes it difficult for this technology to achieve high-performance aluminum nitride ceramic preparation.

Method used

Adhesive spray molding technology, by modifying submicron-scale aluminum nitride powder with polyvinyl butyral and hydrophobic agent, the printing powder is formed, and the adhesive spray is printed and molded, followed by vacuum discharging, impregnation and sintering treatment, and finally high-performance aluminum nitride ceramics are obtained under thermal isostatic pressure conditions.

Benefits of technology

The high-performance aluminum nitride ceramics were successfully prepared through adhesive jet molding technology, which improved its mechanical properties and thermal shock resistance, and ensured the density of the ceramics and the uniformity of the microstructure.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a method for preparing aluminum nitride ceramics by adhesive injection molding technology, and relates to the field of adhesive injection additive manufacturing technology. The preparation method of the present invention adopts submicron aluminum nitride powder for preparation, and the powder is modified by polyvinyl butyral and hydrophobic agent in succession, so as to solve the problem that the aluminum nitride powder reacts with the water-based adhesive and causes the adhesive to hydrolyze, and the aluminum nitride ceramic blank is successfully printed by adhesive injection technology. In addition, the present invention adopts an infiltration process to infiltrate metal ions into the blank after the blank is degreased, so as to increase the density of the blank and successfully introduce the second phase, which is conducive to the preparation of AlN ceramics with high density, fine grains and uniform microstructure, and improves its mechanical properties and thermal shock resistance. The method of the present invention also includes hot isostatic pressing of the sintered body obtained by sintering, which further improves the strength and hardness of the aluminum nitride ceramic, and finally obtains aluminum nitride ceramics with high performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesive jetting additive manufacturing, and in particular to a method for preparing aluminum nitride ceramics by using adhesive jetting molding technology. Background Art

[0002] Aluminum nitride crystal is a covalently bonded compound with 〔AIN4〕tetrahedron as the structural unit. It has a wurtzite structure and belongs to the hexagonal system. It is the only stable compound in the binary Al-N system. The theoretical density is about 3.26g / cm 3 .

[0003] Aluminum nitride ceramics have excellent mechanical properties (hardness of 12GPa at room temperature, bending strength of up to 400MPa), chemical properties (high temperature resistance and corrosion resistance, no need to consider oxidation at room temperature), thermal conductivity (theoretical value of thermal conductivity is about 320W·m -1 ·K -1 ), extremely high insulation (volume resistivity > 1012Ω·m), extremely low dielectric constant (about 8 at 1MHz) and dielectric loss, non-toxicity, and a thermal expansion coefficient that matches that of silicon (4.8×10 -6 K -1 ) and a series of excellent properties, and is considered to be an ideal heat dissipation and packaging material for the new generation of large-scale integrated circuits, semiconductor module circuits and high-power devices.

[0004] Binder Jetting (BJ) is also called Three-Dimensional Printing (3DP). Its principle is to control the nozzle to automatically spray adhesive on the powder plane laid on the two-dimensional plane to selectively bond the powder particles together to form a single layer, and then control the z-axis to sink, then re-lay the material, and then spray the adhesive. Repeat this process to obtain a three-dimensional blank. Binder jetting technology has a wide range of applications, a wide range of material selection (gypsum powder, starch, sand, ceramic powder, metal powder, composite powder, graphene, etc.), fast processing speed, and low manufacturing and operating costs. The production process is not limited by factors such as the shape and structure of the parts, and can complete the manufacture of various complex-shaped parts. However, the blanks formed by this method have poor precision and rough surface, and the prepared parts have low density and low performance.

[0005] However, there is no relevant information on the preparation of aluminum nitride ceramics by adhesive injection molding in the prior art. Summary of the invention

[0006] The technical problem to be solved by the present invention is how to prepare aluminum nitride ceramics by using adhesive injection molding technology.

[0007] In order to solve the above problems, the present invention proposes the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing aluminum nitride ceramics by adhesive injection molding technology, comprising the following steps:

[0009] S1. Mix 85-90 parts by mass of aluminum nitride powder and 1-5 parts of polyvinyl butyral at 80-100° C. under the action of a solvent, and then filter, wash, and dry to obtain modified aluminum nitride powder;

[0010] S2, ball-milling the modified aluminum nitride powder, 1 to 5 parts of a hydrophobic agent, and 1 to 10 parts of a sintering aid, drying, and sieving through 150 to 200 meshes to obtain a printing powder;

[0011] S3, feeding the powder obtained in S2 into an adhesive spraying molding device, and obtaining a green body through adhesive spraying molding;

[0012] S4, solidifying the green body and performing vacuum debinding or atmosphere protection debinding-air debinding two-step debinding treatment;

[0013] S5, completely immersing the debinding body in a metal precursor solution at room temperature for 2 to 4 hours, then soaking it in an ammonia solution for 5 to 15 minutes, taking it out, and drying it for 12 to 48 hours;

[0014] S6, placing the green body dried in S5 in an atmosphere sintering furnace for sintering to obtain a sintered body, and performing hot isostatic pressing on the sintered body to obtain aluminum nitride ceramics.

[0015] It should be noted that the solvent in step S1 can be selected from one or more of n-butanol, anhydrous ethanol, and isopropanol. Under the action of the solvent, assisted by water bath heating, it is helpful to fully mix the aluminum nitride powder and polyvinyl butyral to obtain modified aluminum nitride powder. In step S2, when ball milling the raw materials, a solvent can be added to assist, and a planetary ball mill is used to ball mill at a speed of 200 to 300 rpm for 10 to 12 hours, and the solvent can be removed by drying after the ball milling.

[0016] It should be noted that, before printing, the present invention first modifies the aluminum nitride powder with polyvinyl butyral in step S1, and then adds a hydrophobic agent in step S2 to hydrophobically modify all the powders. This can effectively reduce the saturation of the powder with the glue during printing, and also solves the problem of the aluminum nitride powder reacting with the water-based adhesive to cause the hydrolysis of the adhesive, thereby preventing the hydrolysis of the adhesive before sintering and causing a decrease in the performance of the aluminum nitride ceramic obtained after sintering.

[0017] A further technical solution is that in step S1, the particle size of the aluminum nitride powder is submicron and the particle size distribution is 0.2 to 1 μm.

[0018] It should be noted that the particle size of the aluminum nitride powder selected in the present invention is submicron. This is because: first, compared with nano-level aluminum nitride fine powder, submicron powder has better fluidity, which can ensure the quality of powder spreading during printing and avoid a series of quality problems such as cracks, pores, burrs, etc. caused by uneven powder spreading; secondly, the particle size of the raw material powder remains large enough, and there are sufficient gaps between the particles to allow the adhesive to enter, which is conducive to printing; finally, under the premise of ensuring successful printing, compared with aluminum nitride powder with larger particle size, the submicron aluminum nitride powder selected in the present invention has a denser ceramic part after sintering, which can ensure the good performance of the ceramic part.

[0019] A further technical solution is that the hydrophobic agent is one or more of phosphoric acid, silane coupling agent KH550, DP270, and stearic acid.

[0020] A further technical solution is that the sintering aid is yttrium oxide.

[0021] A further technical solution is that the metal ion in the metal precursor solution is Zr 4+ , Y 3+ ,Mg 2+ At least one of .

[0022] A further technical solution is that the metal precursor solution is prepared by dissolving at least one of zirconium oxychloride octahydrate, yttrium nitrate and magnesium nitrate in anhydrous ethanol.

[0023] A further technical solution is that the metal ion concentration in the metal precursor solution is 0.1-0.3 mol / L.

[0024] It should be noted that the present invention uses an infiltration process to infiltrate metal ions into the green body after degreasing the green body, which helps to increase the density of the green body and successfully introduce the second phase into the green body. The infiltration of metal ions promotes the rearrangement, dissolution-precipitation and grain growth of aluminum nitride ceramic particles, which is beneficial to the preparation of AlN ceramics with high density, fine grains and uniform microstructure, and improves its mechanical properties and thermal shock resistance.

[0025] A further technical solution is that in step S3, the layer thickness of the adhesive jet printing is 100-150 μm.

[0026] A further technical solution is that the specific operation of the vacuum debinding is: placing the green body in a vacuum debinding furnace at -0.1MPa, heating it to 600-1200°C at a rate of 5-10°C / min and keeping it at that temperature for 4-8h, and then cooling the green body to room temperature along with the furnace;

[0027] The specific operation of the atmosphere protection debinding is: placing the green body in a debinding furnace protected by Ar and / or N2, heating it to 600-1200°C at a rate of 5-10°C / min and keeping it at that temperature for 4-8h, and then cooling the green body to room temperature along with the furnace.

[0028] A further technical solution is that the specific operation of air debinding is: placing the green body in a debinding furnace with air atmosphere, heating it to 800-1000°C at a rate of 5-10°C / min and keeping it warm for 2-8h, and then cooling the green body to room temperature along with the furnace.

[0029] A further technical solution is that in step S6, the sintering conditions are: at a N2 flow rate of 0.3-0.8L / min, 1700-1900°C, and keep warm for 6-12h; the specific operation of hot isostatic pressing is to perform hot isostatic pressing on the sintered body for 1-2h at a temperature of 1350-1500°C and a pressure of 100-180MPa under N2 or Ar protective atmosphere.

[0030] It should be noted that, in the present invention, after the green body is sintered and naturally cooled to room temperature, a sintered body is obtained, and then the sintered body is subjected to hot isostatic pressing. The temperature of hot isostatic pressing is 200 to 400°C lower than the sintering temperature, which can prevent abnormal growth of grains in the sintered body and help improve the density, strength and hardness of the ceramic sintered body. For a ceramic sample containing zirconium ions, yttrium ions and magnesium ions in the infiltrated metal precursor solution, XRD phase analysis was performed on it, and the sample contained AlN, YAP, YAG, YAM, a small amount of MgO and a small amount of ZrO2.

[0031] In a second aspect, the present invention provides an aluminum nitride ceramic prepared by the preparation method described in the first aspect.

[0032] Compared with the prior art, the technical effects achieved by the present invention include:

[0033] The method for preparing aluminum nitride ceramics by using adhesive injection molding technology provided by the present invention adopts submicron aluminum nitride powder for preparation, and the powder is modified by polyvinyl butyral and a hydrophobic agent in succession, thereby solving the problem of hydrolysis of the adhesive caused by reaction between the aluminum nitride powder and the water-based adhesive, and successfully using the adhesive injection technology to print out an aluminum nitride ceramic blank.

[0034] Furthermore, the present invention adopts an infiltration process to infiltrate metal ions into the green body after degreasing the green body, so as to increase the density of the green body and successfully introduce the second phase, thereby promoting the rearrangement, dissolution-precipitation and grain growth of particles, which is beneficial to the preparation of AlN ceramics with high density, fine grains and uniform microstructure, and improving its mechanical properties.

[0035] Finally, in the preparation method of the present invention, the sintered body is subjected to hot isostatic pressing, which further improves the strength and hardness of the aluminum nitride ceramic, and finally obtains a high-performance aluminum nitride ceramic that can be prepared by adhesive injection molding technology. DETAILED DESCRIPTION

[0036] The technical solutions in the embodiments are described clearly and completely below. Obviously, the embodiments described below are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] It should be understood that when used in this specification and the appended claims, the terms "include" and "comprises" indicate the presence of described features, integers, steps, operations, but do not exclude the presence or addition of one or more other features, integers, steps, operations and / or groups thereof.

[0038] It should also be understood that the terms used in this description of the embodiments of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the embodiments of the present invention. As used in the description of the embodiments of the present invention and the appended claims, unless the context clearly indicates otherwise, the singular forms of "a", "an" and "the" are intended to include plural forms.

[0039] Example 1

[0040] This embodiment provides a method for preparing aluminum nitride ceramics by adhesive injection molding technology, and the specific steps are as follows:

[0041] 900 g of aluminum nitride powder, 20 g of polyvinyl butyral, 40 g of yttrium oxide (sintering aid), and 40 g of phosphoric acid (hydrophobic agent) were weighed respectively; the aluminum nitride powder had a submicron particle size and a particle size distribution of 0.2 to 1 μm.

[0042] (1) Powder modification:

[0043] First, aluminum nitride powder, polyvinyl butyral and solvent are heated in a water bath and stirred for 60 minutes to fully mix the aluminum nitride powder and polyvinyl butyral, and then the powder is filtered, washed and dried to obtain modified aluminum nitride powder.

[0044] (2) Ball milling and screening:

[0045] The modified aluminum nitride powder, sintering aid, hydrophobic agent and solvent were ball-milled on a planetary ball mill at a speed of 300 rpm for 12 hours to obtain a ceramic slurry. The ceramic slurry was placed in an oven for drying and then passed through a 100-mesh sieve to obtain a printing powder.

[0046] (3) Molding:

[0047] The powder is fed into an adhesive jetting device, and a green body is obtained by adhesive jetting printing, with a layer thickness of 150 μm.

[0048] (4) Debinding:

[0049] The green body is further solidified and subjected to a two-step debinding process of vacuum debinding and air debinding.

[0050] Specifically, the green body is first placed in a negative pressure debinding furnace (vacuum degree ≥ 0.09 MPa), heated to 800 ° C at a rate of 5 ° C / min and kept at this temperature for 8 hours, and then cooled to room temperature with the furnace;

[0051] The green body was then placed in a debinding furnace in an air atmosphere, heated to 800°C at a rate of 10°C / min and kept at that temperature for 6 hours, and then cooled to room temperature in the furnace.

[0052] (5) Infiltration:

[0053] The debinded body was completely immersed in the metal precursor solution at room temperature for 4 hours, and then immersed in an ammonia solution for 10 minutes, and then taken out and dried in an oven for 24 hours.

[0054] The metal precursor solution of this embodiment is an ethanol solution of zirconium oxychloride octahydrate, and the molar concentration is 0.3 mol / L.

[0055] (6) Sintering:

[0056] The green body after drying is placed in an atmosphere sintering furnace for sintering at 1850°C with a N2 flow rate of 0.5 L / min for 6 hours, and then cooled to room temperature with the furnace to obtain a sintered body. The sintered body is subjected to hot isostatic pressing for 2 hours at a temperature of 1600°C and a pressure of 180 MPa under a N2 protective atmosphere to obtain aluminum nitride ceramics.

[0057] The aluminum nitride ceramic prepared by the method of this embodiment has a relative density of 65%, a Vickers hardness of 14.3 GPa, and a thermal conductivity of 130 W / (m·K).

[0058] Example 2

[0059] This embodiment provides a method for preparing aluminum nitride ceramics by adhesive injection molding technology, and the specific steps are as follows:

[0060] 850 g of aluminum nitride powder, 40 g of polyvinyl butyral, 70 g of yttrium oxide (sintering aid), and 40 g of phosphoric acid (hydrophobic agent) were weighed respectively.

[0061] (1) Powder modification:

[0062] First, aluminum nitride powder, polyvinyl butyral and solvent are heated in a water bath and stirred for 60 minutes to fully mix the aluminum nitride powder and polyvinyl butyral, and then the powder is filtered, washed and dried to obtain modified aluminum nitride powder.

[0063] (2) Ball milling and screening:

[0064] The modified aluminum nitride powder was ball-milled with a sintering aid, a hydrophobic agent and a solvent on a planetary ball mill at a rotation speed of 300 rpm for 10 hours to obtain a ceramic slurry. The ceramic slurry was placed in an oven for drying and then passed through a 150-mesh sieve to obtain a printing powder.

[0065] (3) Molding:

[0066] The powder is fed into an adhesive jetting device, and a green body is obtained by adhesive jetting printing, with a layer thickness of 150 μm.

[0067] (4) Debinding:

[0068] The green body is further solidified and subjected to a two-step debinding process of vacuum debinding and air debinding.

[0069] Specifically, the green body is first placed in a negative pressure debinding furnace (vacuum degree ≥ 0.09 MPa), heated to 1000°C at a rate of 10°C / min and kept at this temperature for 4 hours, and then cooled to room temperature along with the furnace;

[0070] The green body was then placed in a debinding furnace in an air atmosphere, heated to 800°C at a rate of 10°C / min and kept at that temperature for 6 hours, and then cooled to room temperature in the furnace.

[0071] (5) Infiltration:

[0072] The debinded body was completely immersed in the metal precursor solution at room temperature for 4 hours, and then immersed in an ammonia solution for 10 minutes, and then taken out and dried in an oven for 24 hours.

[0073] The metal precursor solution of this embodiment is an ethanol solution of zirconium oxychloride octahydrate, and the molar concentration is 0.3 mol / L.

[0074] (6) Sintering:

[0075] The green body after drying is placed in an atmosphere sintering furnace for sintering at 1850°C with a N2 flow rate of 0.5 L / min for 6 hours, and then cooled to room temperature with the furnace to obtain a sintered body. The sintered body is subjected to hot isostatic pressing for 2 hours at a temperature of 1500°C and a pressure of 180 MPa under a N2 protective atmosphere to obtain aluminum nitride ceramics.

[0076] The aluminum nitride ceramic prepared by the method of this embodiment has a relative density of 63%, a Vickers hardness of 12.7 GPa, and a thermal conductivity of 135 W / (m·K).

[0077] Example 3

[0078] This embodiment provides a method for preparing aluminum nitride ceramics by adhesive injection molding technology, and the specific steps are as follows:

[0079] 900 g of aluminum nitride powder, 20 g of polyvinyl butyral, 40 g of yttrium oxide (sintering aid), and 40 g of KH550 (hydrophobic agent) were weighed respectively; the aluminum nitride powder had a submicron particle size and a particle size distribution of 0.2 to 1 μm.

[0080] (1) Powder modification:

[0081] First, aluminum nitride powder, polyvinyl butyral and solvent are heated in a water bath and stirred for 60 minutes to fully mix the aluminum nitride powder and polyvinyl butyral, and then the powder is filtered, washed and dried to obtain modified aluminum nitride powder.

[0082] (2) Ball milling and screening:

[0083] The modified aluminum nitride powder, sintering aid, hydrophobic agent and solvent were ball-milled on a planetary ball mill at a speed of 300 rpm for 12 hours to obtain a ceramic slurry. The ceramic slurry was placed in an oven for drying and then passed through a 100-mesh sieve to obtain a printing powder.

[0084] (3) Molding:

[0085] The powder is fed into an adhesive jetting device, and a green body is obtained by adhesive jetting printing, with a layer thickness of 120 μm.

[0086] (4) Debinding:

[0087] The green body is further solidified and subjected to a two-step debinding process of vacuum debinding and air debinding.

[0088] Specifically, the green body is first placed in a negative pressure debinding furnace (vacuum degree ≥ 0.09 MPa), heated to 800 ° C at a rate of 5 ° C / min and kept at this temperature for 8 hours, and then cooled to room temperature with the furnace;

[0089] The green body was then placed in a debinding furnace in an air atmosphere, heated to 800°C at a rate of 10°C / min and kept at that temperature for 6 hours, and then cooled to room temperature in the furnace.

[0090] (5) Infiltration:

[0091] The debinded body was completely immersed in the metal precursor solution at room temperature for 4 hours, and then immersed in an ammonia solution for 10 minutes, and then taken out and dried in an oven for 24 hours.

[0092] The metal precursor solution of this embodiment is an ethanol solution of zirconium oxychloride octahydrate and magnesium nitrate, and the molar concentration of metal ions is 0.3 mol / L.

[0093] (6) Sintering:

[0094] The green body after drying is placed in an atmosphere sintering furnace for sintering at 1850°C with a N2 flow rate of 0.5 L / min for 6 hours, and then cooled to room temperature with the furnace to obtain a sintered body. The sintered body is subjected to hot isostatic pressing for 2 hours at a temperature of 1600°C and a pressure of 180 MPa under a N2 protective atmosphere to obtain aluminum nitride ceramics.

[0095] The aluminum nitride ceramic prepared by the method of this embodiment has a relative density of 66.7%, a Vickers hardness of 15.2 GPa, and a thermal conductivity of 128 W / (m·K).

[0096] Example 4

[0097] This embodiment provides a method for preparing aluminum nitride ceramics by adhesive injection molding technology, and the specific steps are as follows:

[0098] 900 g of aluminum nitride powder, 20 g of polyvinyl butyral, 40 g of yttrium oxide (sintering aid), and 40 g of stearic acid (hydrophobic agent) were weighed respectively; the aluminum nitride powder had a submicron particle size and a particle size distribution of 0.2 to 1 μm.

[0099] (1) Powder modification:

[0100] First, aluminum nitride powder, polyvinyl butyral and solvent are heated in a water bath and stirred for 60 minutes to fully mix the aluminum nitride powder and polyvinyl butyral, and then the powder is filtered, washed and dried to obtain modified aluminum nitride powder.

[0101] (2) Ball milling and screening:

[0102] The modified aluminum nitride powder, sintering aid, hydrophobic agent and solvent were ball-milled on a planetary ball mill at a speed of 300 rpm for 12 hours to obtain a ceramic slurry. The ceramic slurry was placed in an oven for drying and then passed through a 100-mesh sieve to obtain a printing powder.

[0103] (3) Molding:

[0104] The powder is fed into an adhesive jetting device, and a green body is obtained by adhesive jetting printing, with a layer thickness of 150 μm.

[0105] (4) Debinding:

[0106] The green body is further solidified and subjected to a two-step debinding process of vacuum debinding and air debinding.

[0107] Specifically, the green body is first placed in a negative pressure debinding furnace (vacuum degree ≥ 0.09 MPa), heated to 800 ° C at a rate of 5 ° C / min and kept at this temperature for 8 hours, and then cooled to room temperature with the furnace;

[0108] The green body was then placed in a debinding furnace in an air atmosphere, heated to 800°C at a rate of 10°C / min and kept at that temperature for 6 hours, and then cooled to room temperature in the furnace.

[0109] (5) Infiltration:

[0110] The debinded body was completely immersed in the metal precursor solution at room temperature for 4 hours, and then immersed in an ammonia solution for 10 minutes, and then taken out and dried in an oven for 24 hours.

[0111] The metal precursor solution of this embodiment is an ethanol solution of zirconium oxychloride octahydrate, yttrium nitrate and magnesium nitrate, and the molar concentration of metal ions is 0.3 mol / L.

[0112] (6) Sintering:

[0113] The green body after drying is placed in an atmosphere sintering furnace for sintering at 1850°C with a N2 flow rate of 0.5 L / min for 6 hours, and then cooled to room temperature with the furnace to obtain a sintered body. The sintered body is subjected to hot isostatic pressing for 2 hours at a temperature of 1600°C and a pressure of 180 MPa under a N2 protective atmosphere to obtain aluminum nitride ceramics.

[0114] The aluminum nitride ceramic prepared by the method of this embodiment has a relative density of 64.4%, a Vickers hardness of 14.2 GPa, and a thermal conductivity of 126 W / (m·K).

[0115] Comparative Example 1

[0116] The difference from Example 1 is that the raw material ratio of Comparative Example 1 is 900 g aluminum nitride powder, 20 g polyvinyl butyral, 40 g yttrium oxide (sintering aid), and no hydrophobic agent is included. The hydrophobic agent is missing during the ball milling and sieving process of step (2), and the rest of the preparation process is the same as that of Example 1.

[0117] The relative density of the aluminum nitride ceramic prepared in Comparative Example 1 is 56.8%, the Vickers hardness is 9.8 GPa, and the thermal conductivity is 98 W / (m·K). This is because the aluminum nitride powder is not treated to prevent hydrolysis, so it hydrolyzes with the water-based glue during printing, the oxygen content increases, and the thermal conductivity of the aluminum nitride ceramic after sintering is reduced.

[0118] Comparative Example 2

[0119] Different from Example 1, the raw material ratio of Comparative Example 2 is 900g aluminum nitride powder, 40g yttrium oxide (sintering aid), 40g phosphoric acid (hydrophobic agent), does not contain polyvinyl butyral, lacks (1) powder modification step, and the rest of the preparation process is the same as Example 1.

[0120] The aluminum nitride ceramic body prepared in Comparative Example 2 exhibited delamination after solidification in step (4), and could not be subjected to subsequent debinding and sintering steps.

[0121] Comparative Example 3

[0122] Different from Example 1, in step S3 of Comparative Example 3, the molding process is specifically to feed the powder into the adhesive spraying device, and to obtain the green body by adhesive spraying printing molding, with a layer thickness of 200 μm. The rest of the material ratio and preparation process are the same as those of Example 1.

[0123] The aluminum nitride ceramic body obtained by the method of comparative example 3 was delaminated after curing in step (4), and the subsequent debinding and sintering processes could not be performed. This was because the printing layer thickness value was set too large, and the glue did not completely penetrate the aluminum nitride powder during printing, resulting in an insignificant curing effect between layers.

[0124] Comparative Example 4

[0125] The difference from Example 1 is that the comparative example 4 lacks the infiltration treatment of step S5. That is, after the debinding process of step S4 is completed, the comparative example 4 directly performs sintering to obtain aluminum nitride ceramics. The rest of the material ratios and preparation process are the same as those of Example 1.

[0126] The aluminum nitride ceramic prepared in Comparative Example 4 has a relative density of 50%, a Vickers hardness of 8.3 GPa, and a thermal conductivity of 80 W / (m·K).

[0127] Comparative Example 5

[0128] The difference from Example 1 is that the hot isostatic pressing treatment in step S6 is missing in Comparative Example 5. That is, after the sintering in step S6 is completed, the aluminum nitride ceramic is obtained in Comparative Example 6. The rest of the material ratios and preparation process are the same as those in Example 1.

[0129] The aluminum nitride ceramic prepared in Comparative Example 5 has a relative density of 60%, a Vickers hardness of 11.8 GPa, and a thermal conductivity of 127 W / (m·K).

[0130] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0131] The above is a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of various equivalent modifications or replacements within the technical scope disclosed by the present invention, and these modifications or replacements should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A method for preparing aluminum nitride ceramics by adhesive injection molding technology, characterized in that: The following steps are involved: S1. By weight, 85 to 90 parts of aluminum nitride powder having a particle size distribution of 0.2 to 1 μm and 1 to 5 parts of polyvinyl butyral are mixed at 80 to 100° C. under the action of a solvent, and then filtered, washed, and dried to obtain a modified aluminum nitride powder; S2, ball-milling the modified aluminum nitride powder, 1 to 5 parts of a hydrophobic agent, and 1 to 10 parts of a sintering aid, drying, and sieving through 150 to 200 meshes to obtain a printing powder; S3, feeding the printing powder obtained in S2 into an adhesive spraying molding device, and obtaining a green body through adhesive spraying molding; S4, solidifying the green body and performing vacuum debinding or atmosphere protection debinding-air debinding two-step debinding treatment; S5, completely immerse the debinding body in a metal precursor solution at room temperature for 2 to 4 hours, then soak it in an ammonia solution for 5 to 15 minutes, take it out, and dry it for 12 to 48 hours; the metal ion in the metal precursor solution is Zr 4+ , Y 3+ ,Mg 2+ At least one of; S6, placing the green body dried in S5 in an atmosphere sintering furnace for sintering to obtain a sintered body, and performing hot isostatic pressing on the sintered body to obtain aluminum nitride ceramics; the temperature of the hot isostatic pressing is 200-400° C. lower than the sintering temperature.

2. The method for preparing aluminum nitride ceramics by adhesive injection molding technology according to claim 1, characterized in that: The hydrophobic agent is one or more of phosphoric acid, silane coupling agent KH550, DP270, and stearic acid.

3. The method for preparing aluminum nitride ceramics by adhesive injection molding technology according to claim 1, characterized in that: The sintering aid is yttrium oxide.

4. The method for preparing aluminum nitride ceramics by adhesive injection molding technology according to claim 1, characterized in that: The metal ion concentration in the metal precursor solution is 0.1-0.3 mol / L.

5. The method for preparing aluminum nitride ceramics by adhesive injection molding technology according to claim 1, characterized in that: In the step S3, the thickness of the adhesive spray-molded layer is 100-150 μm.

6. The method for preparing aluminum nitride ceramics by adhesive injection molding technology according to claim 1, characterized in that: The specific operation of the vacuum debinding is: placing the green body in a vacuum debinding furnace at -0.1 MPa, heating it to 600-1200°C at a rate of 5-10°C / min and keeping it at that temperature for 4-8 hours, and then cooling the green body to room temperature along with the furnace; The specific operation of the atmosphere protection debinding is: placing the green body in a debinding furnace protected by Ar and / or N2, heating it to 600-1200°C at a rate of 5-10°C / min and keeping it at that temperature for 4-8 hours, and then cooling the green body to room temperature along with the furnace; The specific operation of air debinding is: placing the green body in a debinding furnace with air atmosphere, heating it to 800-1000°C at a rate of 5-10°C / min and keeping it at that temperature for 2-8 hours, and then cooling the green body to room temperature along with the furnace.

7. The method for preparing aluminum nitride ceramics by adhesive injection molding technology according to claim 1, characterized in that: In the step S6, the sintering conditions are: keeping warm for 6 to 12 hours at 1700 to 1900°C at a N2 flow rate of 0.3 to 0.8 L / min; the specific operation of the hot isostatic pressing treatment is to perform hot isostatic pressing on the sintered body for 1 to 2 hours at a temperature of 1350 to 1500°C and a pressure of 100 to 180 MPa under N2 or Ar protective atmosphere.

8. An aluminum nitride ceramic, characterized in that: Prepared by the method described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method of nitride ceramic

    CN110028324A